Ship Squat in Hydrography - a Study of the Surveying Vessel Deneb - Hàrting, Alexander; Reinking, Jorg; Ellmer, Wilfried (The International Hydrographic Review, 2004)
In hydrographic observations where the water level is used as a reference plane the knowledge of the surveying vessel’s draft is essential. The draft changes dynamically due to the squat effect. A new method called SHIPS was developed for squat estimation of commercial ships and was tested in several experiments on German waterways. In this paper we present an experiment where SHIPS is used to estimate the squat of the German Federal Maritime and Hydrographic Agency’s (BSH) surveying vessel Deneb. The analysis of data results in a description of the squat with an accuracy of 2cm.